The source of lattice rotation in rotating lattice single (RLS) crystals. (1st March 2021) - Musterman, Evan J.; Savytskii, Dmytro; Dierolf, Volkmar; Jain, Himanshu
Abstract: Laser heating can be used to produce single crystal architectures in glass with a lattice that rotates at a constant rate. Such metamaterials can offer properties that are disallowed by conventional crystal structures. To establish the mechanism of this lattice rotation, we used transmission electron microscopy (TEM) to directly observe and characterize dislocations in Sb2 S3 crystal lines fabricated in Sb-S-I glass as a model system. The lattice rotation calculated from the density and Burgers vectors of edge dislocations agrees with lattice rotation values experimentally determined by electron backscatter diffraction (EBSD) and selected area diffraction patterns (SADP). These results provide the first direct proof of the dislocation mechanism of lattice rotation in rotating lattice single (RLS) crystals, and very likely other forms of growth actuated bending, twisting and noncrystallographic branching as seen in spherulites. Graphical abstract: Image, graphical abstract